RESISTANCE EXERCISE IN PREGNANT WOMEN FUNCTIONAL AUTONOMY (Fiep Bulletin - online, 2011)
The study was to investigate the effects of resistance exercise in functional autonomy of pregnant women using a new methodological procedure. The study included 11 pregnant women, not trained, who were selected randomly in the experimental group (EG=six) and control group (CG=five). The experimental group underwent a program of resistance training during nearly 16 weeks in three weekly sessions. The CG was monitored but not subjected to the training program. The two groups were submitted at the beginning and end of the study the following: a) anthropometric measurements, b) test of grip strength of left and right hand, c) stationary march test d) autonomy evaluation test using the tasks - UST, LPB, UDS, RMWDO and CHW. The results of the tests in the final evaluation showed: 1) significant increase in CG time to perform the final evaluation of autonomy; loss of STRENGTH RH and STRENGTH LH and decrease in the number of steps during MARCH; 2) in the EG, the time remained unchanged for the autonomy test, there was no reduction of STRENGTH RH and STRENGTH LH and the MARCH test was recorded better performance of the pregnant woman. At the end of the study, indicators showed that the pregnant women of EG showed to be physically independent to deal with daily life situations, compared with sedentary women in the CG. The tests applied in this pilot study were adequate to assess the functional autonomy of pregnant women in the group.
Keywords: Resistance exercise; Test of functional autonomy; Autonomy in pregnancy